Logistic flows at Alfa Laval - An analysis of the possibilities for optimizing Alfa Laval's airborne freight flows. - Hellgren, Anderz (My University, 2015)
At Alfa Laval there are about 400 000 shipments every year that either go by sea, air, rail or road freight. To date there is no company strategy covering the entire transport domain although there are a lot of projects working on different parts of the problem. The question is how to optimise the transportation system at Alfa Laval and to do that without increasing the transport cost for the company. The problem with delays and possibility for different transport modes will also be addressed. To do this the author has first distinguish the geographical transportation flows to find an applicable area. Then find a suitable theory for optimising the rate between the transportation systems and in the end apply theories on the existing transportation pattern and recommend changes in the freight flows. The geographical partitioning has resulted in a production site in Tumba, Sweden, and was selected as a representative. Furthermore, the analysis has been done on the freights sent by air, both standard and express, to the largest recipients in Asia. The analysis shows that if there is a possibility to change between the different modes of transport an increase in the DOT, delivery-on-time, can be accomplished with 4,4% in average for the freights sent between the different areas.
Keywords: Transportteknik och logistik; Transport; Transport Systems and Logistics; Transport